National Cancer Incidence for the Year 2002 in Korea - Shin, Hai-Rim (Korean Cancer Association, 2007)
PURPOSE: Since the revised Cancer Act of October 2006, cancer registration was reactivated, based on the Statistics Law. MATERIALS AND METHODS: The incidence of cancer during 2002 was calculated on the basis of the information available from the National Cancer Incidence Database. Crude and age-standardized rates were calculated by gender for 18 age groups (0~4, 5~9, 10~14, every five years, 85 years and over). RESULTS: The overall crude incidence rates (CRs) were 269.2 and 212.8 per 100,000 for males and females, and the overall age-standardized incidence rates (ASRs) were 287.8 and 172.9 per 100,000, respectively. Among males, the five leading primary cancer sites were stomach (CR 62.4, ASR 65.7), lung (CR 45.4, ASR 51.0), liver (CR 43.2, ASR 43.7), colon and rectum (CR 30.7, ASR 32.7), and prostate (CR 8.0, ASR 9.6). Among females, the most common cancer sites were breast (CR 33.1, ASR 26.9), followed by stomach (CR 32.8, ASR 26.0), colon and rectum (CR 23.1, ASR 18.5), thyroid (CR 19.1, ASR 15.7), and uterine cervix (CR 18.2, ASR 14.7). In the 0~14 age group, leukemia was the most common cancer for both genders. For males, stomach cancer was the most common cancer in the 15~64 age-group, but lung cancer was more frequent in men 65 or older. For females, thyroid cancer among the 15~34 age-group, breast cancer among 35~64 age-group and stomach cancer in women 65 years or older were the most common forms of cancer for each age group. The quality indices for the percentage of deaths, by death certificate only, were 4.7% for males and 4.5% for females. CONCLUSIONS: Since the National Cancer Incidence Database was started, the annual percent change of cancer cases increased by 4.8% (4.1% for males, 5.7% for females) during 1999~2002. This value reflects the increase in prostate cancer for males and breast and thyroid cancer in females during 2002. The timely reporting of improved quality of cancer registration is needed for evidence-based decisions regarding cancer control in Korea.